Interactive communicative discourse in the Holy Qur’an: A deliberative approach - Abouelnour, Moustafa Mohamed; Alhourani, Mohammad Issa; Adel, Mohammed Ahmed Abou; Hamwy, Rania; ALQaidy, Amna Musabbeh; Qaruty, Reema Al (Edelweiss Applied Science and Technology, 2024)
Quranic discourse is considered one of the most important linguistic patterns and a significant source for learning and communication in the Islamic world. It is characterized by its interactive nature and ability to effectively communicate with the target audience. Therefore, this research aims to analyze the interactive communicative discourse in the Holy Quran, understand the nature of this discourse, and study its features and effects on listeners pragmatically. This will be achieved through examining random samples of Quranic texts that include examples of interactive communicative discourse, and analyzing these texts in terms of context, linguistic structure, and communicative techniques used. This research is expected to contribute to enriching our understanding of the interactive communicative discourse in the Holy Quran and its impact on listeners. The results will also contribute to developing methods of interpretation and communication of the Holy Quran, as well as enhancing its understanding and application in Islamic society.